2013
DOI: 10.7870/cjcmh-2013-025
|View full text |Cite
|
Sign up to set email alerts
|

Unheard Voices: Mothers of Adult Children With Schizophrenia Speak Up

Abstract: the occupations of a mother are significantly disturbed or restricted when her child is diagnosed with schizophrenia. emerging family-centred practice models consider the role of mothers as caregivers, but do not adequately address their personal needs. this qualitative study explores the occupational challenges faced by mothers as they navigate the experience, highlighting the impact of the devastating experience of having a child diagnosed with schizophrenia, and draws attention to the need for improved meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Research published by Johansson et al (2015) revealed that the health of mothers was affected to a greater extent than fathers. Mothers expressed more concerns about the impact of their child's illness on the family (Landon et al, 2016;White & Unruh, 2013) and experienced a sense of bereavement (Wiens & Daniluk, 2017) upon hearing their child's diagnoses. Their grief can be described as nonfinite because it was never ending, denying them of the hopes, dreams, and aspirations they once held for their child (Schultz & Harris, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research published by Johansson et al (2015) revealed that the health of mothers was affected to a greater extent than fathers. Mothers expressed more concerns about the impact of their child's illness on the family (Landon et al, 2016;White & Unruh, 2013) and experienced a sense of bereavement (Wiens & Daniluk, 2017) upon hearing their child's diagnoses. Their grief can be described as nonfinite because it was never ending, denying them of the hopes, dreams, and aspirations they once held for their child (Schultz & Harris, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Parents had an emotional investment in their child which is typically infused with hopes and dreams for their children's future. Though the degree of specificity varied, parents typically wanted their children to live happy, healthy, and fulfilled adult lives (Johansson et al, 2012;White & Unruh, 2013;Wiens & Daniluk, 2009). When their adult child was diagnosed with SMI, parents in these studies realized that those hopes and dreams might not be possible.…”
Section: Resultsmentioning
confidence: 99%
“…Parents also needed to adjust their own relationship with their adult child. At a time when parents were looking forward to launching their young adult child, they now needed to rethink how they would continue in some sort of caregiving role for the foreseeable future (Darmi et al, 2017;Johansson et al, 2010;Landon et al, 2016;White & Unruh, 2013). Parents had to thereby adjust the hopes and dreams they had for themselves at this stage of life.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations